Pancreas Divisum in Children and Duodenum-Preserving Resection of the Pancreatic Head - Snajdauf, Jiri; Petru, Ondrej; Nahlovsky, Jiri; Rygl, Michal; Frybova, Barbora; Bronsky, Jiri; Mixa, Vladimir; Keil, Radan (European journal of pediatric surgery, 2018)
INTRODUCTION: A retrospective study was performed to evaluate the clinical features, diagnostic methods, and treatment alternatives in children with pancreas divisum (PD). MATERIALS AND METHODS: Patients who underwent treatment for PD between 1999 and 2014 at our department were evaluated for sex, age, presenting symptoms, physical examination findings, biochemical markers, diagnostic methods, treatment modalities, and results of treatment during follow-up. RESULTS: Seven patients who underwent treatment of symptomatic PD were included in the study. The median for follow-up period was 8 years (from 26 months to 16 years). Male-to-female ratio was 4:3 and the median age at presentation was 11 years (2-14 years). Presenting symptoms were recurrent episodic epigastric pain. Pancreatitis was documented by elevated amylase or lipase levels. Endoscopic retrograde cholangiopancreatography (ERCP) was the method of diagnosis of PD in all patients. Five patients had complete PD and two had incomplete variants. Three patients improved after ERCP papillotomy. In three patients, papillotomy was unsuccessful but they have only mild episodes of pancreatitis. One patient presented at the age of 4 years with recurrent pancreatitis. She was treated surgically by duodenum-preserving resection of the pancreatic head (DPRPH) because of severe recurrent pancreatitis occurring even after ERCP papillotomy. The patient is 26 months after operation without any reported problems. CONCLUSION: Patients with symptomatic PD are indicated for ERCP papillotomy attempt. If there is not improvement after ERCP, then recurrent bouts of severe pancreatitis are considered as an indication for surgical procedure. DPRPH is a safe and feasible surgical alternative.
Keywords: nemoci slinivky břišní; Pancreatectomy; pankreatektomie; Humans; dítě; Child; Duodenum; Female; výsledek terapie; lidé; mladiství; pankreas; Pancreas; Cholangiopancreatography, Endoscopic Retrograde; předškolní dítě; duodenum; Follow-Up Studies; ženské pohlaví; Male; cholangiopankreatografie endoskopická retrográdní; Pancreatic Diseases; Retrospective Studies; Adolescent; Treatment Outcome; retrospektivní studie; mužské pohlaví; Child, Preschool; Sphincterotomy, Endoscopic; následné studie; sfinkterotomie endoskopická